ANALISA DESAIN KARAKTER PADA KOMIK “NUSA FIVE” - Octavianus Bramantha (Universitas Mercu Buana, 2020)
In the development of the digital world today, comics have become one of the most rapidly developing works of art, because the increasingly depleted problem of comic artists in publishing their work, many new comic artists have sprung up abroad and in the country. It is